Learning to interpret one's own outcome as unjustified amplifies altruistic compensation: a training study - Maltese, Simona; Baumert, Anna; Knab, Nadine; Schmitt, Manfred J. (Frontiers in Psychology, 2013)
Interpretational tendencies in ambiguous situations were investigated as causal mechanisms of altruistic compensation. We used a training procedure to induce a tendency to interpret one’s own advantages as unjustified. In a subsequent mixed-game, participants had to decide whether to invest their own money to compensate a victim of a norm violation. The amount of one’s own resources invested as an altruistic compensation was enhanced after the training procedure compared to controls. These findings suggest that interpretational patterns with regard to injustice determine prosocial behavior. The training procedure offers a potential intervention strategy for enhancing altruistic compensation in bystander situations in which people must invest their own resources to restore justice.